Pharmacoeconomic Analysis of Treatment Regimens for Coronavirus Infection Coronavirus Disease-19 - Krylova, Olga; Krasheninnikov, Anatoliy; Mamontova, Elza; Tananakina, Galina; Belyakova, D. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: In March 2020, the coronavirus disease (COVID-19) infection was assigned the status of a pandemic. As of the beginning of 2021, the Russian Federation ranks fourth in terms of the prevalence of coronavirus infection. Over the period from March 2020 to February 2021, more than 84,000 fatal cases of the disease were recorded in Russia. AIM: However, at the moment, there are no medications with proven effectiveness and safety against the novel coronavirus infection. In this regard, the purpose of our study was to conduct a pharmacoeconomic analysis of medications for etiotropic therapy of all forms of COVID-19 recommended by the Ministry of Health of the Russian Federation (clinical guidelines, version 10 dated February 8, 2021) to identify the best treatment option. MATERIALS AND METHODS: In the course of the study, the “cost of illness” was determined for all forms of the disease in an outpatient and inpatient setting. The authors took into account the direct medical costs of medication therapy and diagnostic and treatment procedures. In terms of direct non-medical costs, they calculated the cost of a bed-day excluding medication treatment, and indirect costs included payments for temporary disability sheets. Costs for medications were calculated based on the active ingredient (AI) and the packages for treatment on an outpatient basis and in the case of the hospital setting based on the AI only. The cost of medical and diagnostic procedures was determined based on the Tariff Agreement for 2020 dated December 30, 2019. Next, a cost-effectiveness analysis was performed. Effectiveness criteria were selected based on published clinical trial results for the medications in question. Then, they performed a calculation of the cost-effectiveness coefficients and an incremental analysis. RESULTS: Thus, in the course of the analysis of the cost of illness, the most economically profitable treatment regimens were the ones with hydroxychloroquine both for outpatient treatment (13,150.31 rubles: Mild form, 22,326.44 rubles: Moderate form excluding antibiotic therapy, and 21,513.76 rubles: Moderate form, taking into account antibacterial therapy) and for inpatient treatment (34,441.53 rubles). CONCLUSION: As a result of the cost-effectiveness analysis, the use of favipiravir can be considered optimal (comparative effectiveness research = 17,607.14 rubles), and for the mild form, the optimal medication is umifenovir, since during the incremental analysis, it was found that for therapy with favipiravir, 100 people would need an additional allocation of 96.291 rubles, which, given the form of the disease, is not entirely appropriate.